Plasmodium falciparum remains the dominant parasite affecting children despite decades of implementing vector control in two villages of Wolaita Zone, Southwest Ethiopia - Elias, Shimels; Massebo, Fekadu (Frontiers in Epidemiology, 2024)
Background: Malaria is still a significant public health concern, and its prevention and control measures have different impacts in different areas. This study assesses the prevalence of malaria and the effectiveness of routine malaria control programmes such as indoor residual spray (IRS) in two Ethiopian villages.The Kebeles (villages) were purposefully selected based on their malaria prevalence rates. A parasitology survey was conducted in Fango-Gelchecha pre-and post-IRS implementation, whereas in Shochora-Abela it was only conducted post-IRS implementation. The IRS was implemented as part of the routine malaria control programme in August 2017. Every fourth house from the village registration list was systematically selected, resulting in a sample of 300 households per village. A total of 3075 individuals were enrolled for malaria testing using microscopy.Results: After three to four months of application of IRS in August 2017, 59 malaria cases were confirmed, resulting in an overall prevalence of 1.9% (95% CI: 1.5-2.5). Of the positive cases, 18 cases (0.59%: 95% CI: 1.3-1.8) were from Shochora-Abela village, and 41 cases (1.33%: 95% CI: 1.1-1.3) were from Fango-Gelchecha. About age categories, the prevalence of malaria was 10.1% (95% CI: 5.9-15.9) among children under five, 4.7% (95% CI: 3.3-6.4) in children aged 5-14, and only 0.32% (95% CI: 0.13-0.67) in the age group 15 and above. Overall, P. falciparum was the dominant malaria parasite, accounting for 69.5% (95% CI: 56.1-80.8), while P. vivax malaria accounted for 30.5% (95% CI: 19.2-43.8). The malaria prevalence in Fango-Gelchecha village was 3.1% (95% CI: 2.3-4.0) before IRS and 2.6% (95% CI: 1.8-3.5) after IRS application. In the village of Shochora-Abela, the prevalence of malaria post-IRS was 1.2% (95% CI: 0.7-1.9), but the prevalence prior to IRS was not evaluated.Conclusions: Plasmodium falciparum is the predominant parasite in the villages, mainly affecting children under five. Therefore, protecting young children should be the top priority for reducing infection burdens.